Psoralea corylifolia extract induces vasodilation in rat arteries through both endothelium-dependent and -independent mechanisms involving inhibition of TRPC3 channel activity and elaboration of prostaglandin - Addis Kassahun Gebremeskel; Tharaka Darshana Wijerathne; Ji Hyun Kim; Min Ji Kim; Chang-Seob Seo; Hyeun-Kyoo Shin; Kyu Pil Lee (Taylor & Francis Group, 2017)
Context: Fructus Psoralea, Psoralea corylifolia L. (Leguminosae), has been widely used in traditional medicines for the treatment of dermatitis, leukoderma, asthma and osteoporosis. Objectives: In this study, we sought to study mechanisms underlying the vasoactive properties of Psoralea corylifolia extract (PCE) and its active ingredients. Materials and methods: To study mechanisms underlying the vasoactive properties of PCE prepared by extracting dried seeds of Psoralea corylifolia with 70% ethanol, isometric tension recordings of rat aortic rings and the ionic currents through TRPC3 (transient receptor potential canonical 3) channels were measured with the cumulative concentration (10-600 μg/mL) of PCE or its constituents. Results: Cumulative treatment with PCE caused the relaxation of pre-contracted aortic rings in the presence and absence of endothelium with EC50 values of 61.27 ± 3.11 and 211.13 ± 18.74 μg/mL, respectively. Pretreatment with inhibitors of nitric oxide (NO) synthase, guanylate cyclase, or cyclooxygenase and pyrazole 3, a selective TRPC3 channel blocker, significantly decreased PCE-induced vasorelaxation (p < 0.01). The PCE constituents, bakuchiol, isobavachalcone, isopsoralen and psoralen, inhibited hTRPC3 currents (inhibited by 40.6 ± 2.7, 27.1 ± 7.9, 35.1 ± 4.8 and 47.4 ± 3.9%, respectively). Furthermore, these constituents significantly relaxed pre-contracted aortic rings (EC50 128.9, 4.5, 32.1 and 114.9 μg/mL, respectively). Discussion and conclusions: Taken together, our data indicate that the vasodilatory actions of PCE are dependent on endothelial NO/cGMP and also involved in prostaglandin production. PCE and its active constituents, bakuchiol, isobavachalcone, isopsoralen and psoralen, caused dose-dependent inhibition of TRPC3 channels, indicating that those ingredients attenuate Phe-induced vasoconstriction.